Design Of An Expert System For The Diagnosis Of Tuberculosis (TBC) Using The Visual Basic Forward Chaining Method - Cahya Ari Setiabudi; Agus Suryana (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
One of the infectious diseases that is currently still a global concern is Tuberculosis or what is often called TB. Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Making this expert system aims to produce a system that is capable of making a diagnosis that can provide a quick and accurate decision for tuberculosis sufferers with ease of use and provide solutions/suggestions according to the type of TB disease. The method used in this study uses the forward chaining method, which is an inference method that does reasoning from a problem to its solution. If the premise clause matches the situation (values TRUE), then the process will state the conclusion. The implementation of this expert system program goes well and provides the right solution for users.